THE IMMUNOSTIMULAN POTENTIAL OF TENGGULUN (PROTIUM JAVANICUM) LEAVES TOWARDS T CELL CD4+ AND IFNÎ³ SECRETION ON PBMC CHICKEN - Jayawardhana, Andi; Puspitasari, Heni; Meles, Dewa Ketut; Koesdarto, Setiawan (Indonesian Journal of Tropical and Infectious Disease, 2016)
One of the plants with immunostimulant activity is Tenggulun leaves which contain of flavonoid, like terpenoid. The aim of this research is to find the potential of Tenggulun's leaves extract to have the immunostimulant activities. The potential of immunostimulant activity is identified by the increasing the amount of T-cell CD4+ expression and IFNÎ³ secretion. The research method is conducted through cultured chicken PBMC which is infected by ND virus; it is then treated with Tenggulun's leaves extract with immunostimulant. The result of immunocitochemistry examination CD4+ secretion on PBMC cultures shows how tenggulun is significantly different from the control in the secretion CD4+. The 10Î¼g of tenggulun extract can modulate the T cell CD4+ secretion 68.8±0.83. It is significantly different from K (control) (p<0,05) and treatment group K+, P0, and P1. The examination of IFNÎ³ level using ELISA from tenggulun leaves extract of 10Î¼g doses were inoculated after being infected by ND virus contained immonostimulant potential in increasing the secretion of IFNÎ³ 120.91±6.44. It is significantly different from K-, K+, and P1, yet not significantly different from P0. The content of terpenoid can increase IFNÎ³ secretion on the macrofag cells culture and limfosit cells.